A paradigm shift in CO tolerant catalyst design for fuel cells via introducing defect-controlled carbon molecular sieve layers. (October 2022) - Min, Jiho; Kim, Sungmin; Jeffery, Arokia Anto; Shin, Hyeyoung; Kang, Yun Sik; Kim, Youngjin; Jang, Jeonghee; Lee, Seunghyun; Park, Seok-Hee; Park, Gu-Gon; Yoo, Sung Jong; Yim, Sung-Dae; et al.
Abstract: The CO poisoning effect leads to serious performance degradation of polymer electrolyte membrane fuel cells using reformed H2 as fuel. To address this problem, PtRu-based catalysts have been extensively studied over decades. Nevertheless, the catalyst stability issue due to Ru dissolution has always risen to the surface. Here, we propose a solution to simultaneously achieve high CO tolerance and stability of PtRu catalysts via introducing a defect-controlled carbon molecular sieve layer. The ultrathin carbon shell with controlled pore structures allows for the selective permeation of H2, providing exceptionally high CO tolerance. The molecular sieve effect is demonstrated even by Ru-free Pt nanoparticles with carbon shells. The carbon shell-encapsulated PtRu nanoparticles also show remarkably improved stability due to the protective carbon layer. This atomic-scale molecular sieve effect is expected to bring about a radical change in the design of CO tolerant catalyst structures that have been entirely dependent on metal composition. Graphical abstract: We propose a novel molecular sieve effect to replace the bi-functional effect by introducing a carbon shell on the metal surface to improve the CO-tolerance and durability of fuel cells. Image 1 Highlights: Development of molecular sieve effect-based CO tolerant fuel cell catalysts. Bottom-up synthesis of ultrathin molecular sieve layer-coated metal nanoparticles. Fine control of the structure of carbon molecular sieve layers at the atomic level. Demonstration of molecular sieve effect through experiments and DFT calculations. Enhanced CO tolerance and durability of catalysts for fuel cells using reformed H2 .